Plant Characteristics and Bulb Yield of Onion as influenced by Farmyard Manure and Potassium Application Under Maize-based Cropping System at Dailekh - Luitel, Binod Prasad; Bhusal, Yubaraj; Bhandari, Bishnu Bahadur (Agriculture Development Journal, 2024)
This study was conducted to investigate the effect of different levels of farm yard manure (FYM) (0, 10 and 20 t/ha) and potassium (K2O) fertilization (0, 30, 60 and 90 kg/ha) on plant characteristics and bulb yield of onion cv. ‘Red Creole’ at Horticulture Research Station (HRS), Dailekh during two consecutive years (2019 and 2020). Experiments were laid out in factorial randomized complete block design with three replications. The combined analysis revealed that FYM significantly affected on plant height, number of leaves/plant, leaf length, bulb diameter, bulb weight and bulb yield. But the significant effect of K2O was observed on plant height, number of leaves/plant, leaf length, bulb weight and bulb yield. The highest bulb yield (37.4 t/ha) was recorded at the treatment of 10 t/ha FYM, whereas K2O fertilization at 90 kg/ha produced the highest (39.9 t/ha) bulb yield. The combined application of 10 t/ha FYM and 30 kg/ha K2O produced the highest (41.7 t/ha) bulb yield and found the best treatment combination from the benefit cost ratio analysis. Therefore, the combination of 10 t/ha FYM with 30 kg/ha K2O can be recommended to apply at the soils having medium organic matter and high K2O content to get the highest bulb yield at maize-based cropping system of upland condition in Dailekh.